2015
DOI: 10.1177/0363546514567061
|View full text |Cite
|
Sign up to set email alerts
|

Length Change Behavior of Virtual Medial Patellofemoral Ligament Fibers During In Vivo Knee Flexion

Abstract: The results for lengths and length change patterns of various MPFL fibers are expected to serve as a theoretical background for anatomic double-bundle MPFL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 36 publications
5
40
0
Order By: Relevance
“…Our findings confirm that the MPFL is not a fully isometric structure [9,13]. We measured a considerable length change with a maximal string length difference throughout full range of motion of 9.8 mm for string I and 7.2 mm for string II.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings confirm that the MPFL is not a fully isometric structure [9,13]. We measured a considerable length change with a maximal string length difference throughout full range of motion of 9.8 mm for string I and 7.2 mm for string II.…”
Section: Discussionsupporting
confidence: 82%
“…This anatomic structure represents an important passive stabilizer in early flexion degrees in patellofemoral joint kinematics [9][10][11][12][13]; it prohibits the patella from being laterally misrouted near knee extension in the proximal, mostly dysplastic, trochlear portion.…”
Section: Introductionmentioning
confidence: 99%
“…9) [30,33,39] in passive knee flexion. Thereby, the validity of our musculoskeletal model and the reliability of the multibody simulation could be verified.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, both groups defined optimal insertion points for MPFL reconstruction and highlighted the importance of anatomical insertion. The calculation of MPFL length change pattern with respect to five patellar insertions and the anatomic femoral insertion point was investigated in detail [30]. Furthermore, it has been tried to transfer the computation of the optimal MPFL length change pattern into clinical practice in order to find the ideal, patient-specific femoral attachment point [22].…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies using computational models reconstructed from imaging data of subjects indicated that graft tension would be expected to decrease with flexion, 29 decrease in early flexion followed by an increase, 30 or increase in early flexion followed by a decrease. 31 The studies based on path length between graft attachment points did not account for all of the anatomical factors that contribute to patellar instability or patellar glide allowed intraoperatively.…”
mentioning
confidence: 99%